DETERMINATION OF STATUS AS A WITNESS OF COOPERATING ACTORS (JUSTICE COLLABORATOR) AND THE RIGHT TO CRIMINAL LENIENCY IN THE LAWS AND REGULATIONS IN INDONESIA - Esti Aryani; Triwanto Triwanto (Wacana Hukum, 2021)
The objective of this research as to analize judge’s consideration in determining the justice collaborator. This research is a normative legal research using case study approach. This research will examine court reasoning or consideration in order to reach decision. The research prioritizes literature review by data compiling originating from library and other source.The research result finds that there is no similar understanding amongst law enforcers in applying legislation so that it needs a forum to create similar understanding amongst law enforcers in reading and applying regulation of justice collaborator, in order to get certainty for the suspect or the accused who is willing to become a justice collaborator that he/she will have leniency of criminal penalties. This will encourage the suspect or the defendant to cooperate in revealing the criminal act of corruption completely.